2022
DOI: 10.1042/cs20210470
|View full text |Cite
|
Sign up to set email alerts
|

The HDAC2/SP1/miR-205 feedback loop contributes to tubular epithelial cell extracellular matrix production in diabetic kidney disease

Abstract: Extracellular matrix (ECM) accumulation is considered an important pathological feature of diabetic kidney disease (DKD). Histone deacetylase (HDAC) inhibitors protect against kidney injury. However, the potential mechanisms of HDACs in DKD are still largely unknown. Here, we describe a novel feedback loop composed of HDAC2 and miR-205 that regulates ECM production in tubular epithelial cells in individuals with DKD. We found that HDAC2 mRNA expression in peripheral blood was markedly higher in patients with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…MiRNAs are well-known for regulating gene expression at the post-transcriptional level by pairing with target sequences in the 3 0 untranslated region of mRNAs. The endogenously expressed miRNAs play important roles in many physiological and pathological processes [25]. MiR-205 was epigenetically regulated by HDAC2 through an Sp1-mediated pathway [25].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…MiRNAs are well-known for regulating gene expression at the post-transcriptional level by pairing with target sequences in the 3 0 untranslated region of mRNAs. The endogenously expressed miRNAs play important roles in many physiological and pathological processes [25]. MiR-205 was epigenetically regulated by HDAC2 through an Sp1-mediated pathway [25].…”
Section: Plos Onementioning
confidence: 99%
“…The endogenously expressed miRNAs play important roles in many physiological and pathological processes [25]. MiR-205 was epigenetically regulated by HDAC2 through an Sp1-mediated pathway [25]. MiR-7a/b protected against cardiac remodeling and hypoxia-induced injury in H9c2 cardiomyoblasts involving Sp1 and PARP-1 [26].…”
Section: Plos Onementioning
confidence: 99%
“…At the same time, HDAC2 reduces histone H3K9 acetylation in the miR-205 promoter and inhibits its expression through an SP1-mediated pathway. miR-205 also regulates its own transcription by inhibiting HDAC2 and increasing histone H3K9 acetylation in its promoter, forming a feedback regulatory loop [ 138 ]. Similarly, miR-376a and HDAC9 form a regulatory circuitry in hepatocellular carcinoma: HDAC9, which is a direct target of miR-376a, also increases the expression of miR-376a by upregulating the global histone H3K18 acetylation level [ 141 ].…”
Section: Histone Modifications and Ncrnas: The Theorymentioning
confidence: 99%
“…Previously study has been suggested that miR‐205 can relieve the renal fibrosis in mice. [ 11 ] By bioinformatic analysis, we discovered that lncRNA SNHG16 had the mutual binding sites of miR‐205. Based on this, this work established a unilateral ureteral obstruction (UUO)‐induced mouse renal fibrosis model, and explored whether lncRNA SNHG16 regulated the progression of renal fibrosis by targeting miR‐205.…”
Section: Introductionmentioning
confidence: 99%